The Psychometric Properties of the Norwegian version of ADHD Rating Scale ADHD Rating Scale – IV: Home Version - Kornør, Hege; Bøe, Tormod (PsykTestBarn, 2011)
Description: ADHD-RS-IV Home is a questionnaire to be completed by mothers, fathers, guardians or grandparents to detect ADHD symptoms in children and adolescents. The questionnaire contains 18 items, each with four answer options. It takes less than 20 minutes to complete. Item scores are summed up to score the total scale and the two subscales. Those who administer the ADHD-RS-IV should have general training in test use, as well as a professional status as psychologist, physician, or other health workers or teachers with education at the master degree level. Literature search: Our systematic literature search identified four publications from four Norwegian studies. Psychometrics: One study with a small sample reported Cronbach’s α = 0.73, and test-retest intra class coefficient (ICC) = 0.95. None of the included publications reported norms or validity details for the ADHD-RS-IV Home. Conclusion: The internal consistency of the ADHD-RS-IV Home was adequate and the test-retest reliability was excellent, but the sample size was inadequate and adds great uncertainty to these measures. There is no evidence for norms or validity of the Norwegian version of the ADHD-RS-IV Home.